ESG INTEGRATION AND FINANCIAL OUTCOMES IN EMERGING MARKETS: A PANEL DATA ANALYSIS (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
Over the past two decades, the significance of  responsible investing has surged, prompting a  focus on understanding the interaction between  Environmental, Social, and Governance (ESG)  factors. This study investigates the relationship  between stock returns, investment performance,  and ESG considerations as investors increasingly  prioritize sustainability in their decision-making  processes. By analyzing a sample of NIFTY  50 companies listed on the National Stock  Exchange (NSE), this research delves into how  ESG factors influence stock returns and financial  performance. Employing a comprehensive  methodology, this study expands on previous  research by incorporating financial performance  metrics alongside stock returns. It seeks to shed  light on the nuanced dynamics between ESG  performance and financial outcomes within the  context of NIFTY 50 companies. The FEM  regression method was employed to examine  how ESG rating affected corporate financial  performance and stock returns. Notably, the  findings underscore the substantial impact of  environmental sustainability on stock returns  and financial performance, reinforcing previous  research in this area. Furthermore, the study  highlights the significance of individual ESG  components, including corporate governance  standards and environmental regulations, in  shaping investment outcomes. By elucidating  the intricate relationship between ESG factors  and financial performance, this research  contributes valuable insights to the body of  knowledge surrounding sustainable investing.
Keywords: ESG factors; financial performance; sustainability; corporate governance; environmental regulations